Vigilância em Saúde de Populações Expostas a Agrotóxicos - Conceição Pereira, Farida; Piccirillo B. da Veiga, Denise; Sergio O. Valentim, Luís; Norie Inamine, Rosemairy; Taiveron de Souza, Márcia; Gimenez Lopes, Luana Gimenez Lopes; José Mario Junior, Rubens; de Lelis Andrade Morais, Isabel; Tranquillini Rezende, Cristiane Maria (BEPA. Boletim Epidemiológico Paulista, 2021)
.